ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN MASYARAKAT TRANSMIGRAN DI TRANS SAKATO JAYA KECAMATAN SUNGAI AUR KABUPATEN PASAMAN BARAT - Yulianti, ND.; Ansofino, Ansofino; Jolianis, Jolianis (Pendidikan Ekonomi, 2014)
ABSTRAC Issues that are examined in this study was the effect of capital , level of education , health , the amount of production and labor costs to the community income migrants in Trans Sakato Jaya Kecamatan Sungai AurKabupaten West Pasaman . Analysis using multiple regression significance test using the t test and F test while the test using test Multikolonieritas asumsiklasik , heterokedastisitas test,normality test and autocorrelation test . The results showed that the First : Capital ( X1 ) does not affect the income of the people in the Trans Transmigrants Sakato Jaya Kecamatan Sungai Aur . This is indicated by the capital value of the coefficient of -0.164 with a prob value of 0.129 . Means any capital increase by 1 %, then the income will be decreased by Rp 0.164 . Second : The level of education ( X2 ) significant and positive impact on peoples income Migrants in Trans SakatoJaya Kecamatan Sungai Aur . This is indicated by the value of the coefficient of education level of 256,107.7 . Means any increase in the education level of 1% then the revenue would have increased by Rp 256,107.7 Third : Health ( X3 ) significant and positive impact on peoples income Migrants in Trans Sakato Jaya Kecamatan Sungai Aur. This is indicated by the value of the coefficient of Health 20235.9 . Means any increase in the education level of 1% then the revenue will increase by USD 20235.9 . Fourth : Total production ( X4 ) significant and positive impact on peoples income Migrants in Trans Sakato Jaya Kecamatan Sungai Aur. This is indicated by the value of the coefficient of total production of 3976.16 . Means any increase in the amount of 1% of production revenue will increase by U.S. 3976.16 . Fifth : Wage labor ( X5 ) does not affect the income of the people in the Trans Transmigrants Sakato Aur Jaya River District . This is indicated by the value of the coefficient of wage labor at 0.016 with prob value of 0.636 . Sixth capital , level of education , health , the amount of production , and wage labor , jointly affect peoples income migrants in trans sakato victorious in the show with this prob value of 0.000 is smaller than 0.05 .